Spiritual Emotional Freedom Technique (SEFT) Therapy in Reducing Student Anxiety Levels - Indah Roziah Cholilah (Jurnal Al-Hikmah, 2023)
Students are vulnerable to experiencing anxiety disorders, given the complexity of their developmental tasks as adult individuals. Personal desires and the demands of the social environment often lead to anxiety and even depression. If this condition persists throughout their lifetime, it can be harmful to students. Therefore, psychological intervention through SEFT (Spiritual Emotional Freedom Technique) therapy is necessary to help alleviate the anxiety experienced by students. This research aims to assess the effectiveness of SEFT (Spiritual Emotional Freedom Technique) in reducing anxiety in students of the Islamic Psychology Study Program, Faculty of Dakwah, UIN KH. Achmad Siddiq Jember. The research method employs a quasi-experimental design with a non-random one group pre and post-test. The sample for this study consists of 30 students from the Islamic Psychology Study Program, class of 2018 to 2020, both male and female, who experience anxiety. The sampling technique used is purposive sampling. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) and statistical analysis was performed using the paired sample t-test. The data analysis revealed a coefficient value of t = 9.625 at p = 0.000 (p < 0.05), indicating a significant difference in anxiety levels before and after SEFT therapy. Therefore, it can be concluded that SEFT has been proven effective in reducing anxiety levels in students.